Designing a suitable model to transfer the effect of primary to secondary students - Aminfar, Mahdi; Arabhashemi, Malihe; Mazbouhi , Saeid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Studies show that students who move from familiar schools to unknown areas may have problems in the learning process due to temporary disorders. This research aims to design a suitable model to transfer the effect of elementary school students to secondary school. Method: This research, which is considered to be a type of qualitative research, has been theorized with an inductive approach and using the research strategy of Foundation Data Theory and Strauss-Corbin Systematic Design. The community in the qualitative section includes experts, consultants and experts in the field of lesson planning who were interviewed. The sampling method was purposeful sampling and semi-structured interviews were conducted with 12 experts, consultants and experts to collect information and reach theoretical saturation. The key points of the interviews were analyzed during the three stages of open, central and selective coding. For the validity and reliability of the research, review by members, participation, triangulation and retest reliability were used. Results: Finally, a suitable model was designed to transfer the effect of primary to secondary students with 51 categories and 167 concepts. Therefore, the model obtained from this research can be used for education decision-makers, families and schools and help improve elementary school students’ effective transition to secondary school. Conclusion: considering goals such as transfer advantages, student independence, reduction of bureaucracy in high school, reduction of inconsistencies, reduction of organizational barriers, reduction of educational barriers, reduction of personal barriers, reduction of environmental barriers, communication with peers, reduction of social barriers, recreational goals, flexible and not long classes can achieve results such as clarifying the dimensions of transition for students, relaxing high school environment, reducing fear, connecting with old friends, creating motivation, finding new friends